O uso de simulação na análise de sistemas de produção - Coelho de Alvarenga , Sônia; Batista de Oliveira , Evonir (Revista Ceres, 2025)
This study is an evaluation of the simulation technique applied to the analysis of production systems for beef cattle in the State of Minas Gerais.